Indoor localization and tracking based on received signal strength in wireless sensor networks - Ng, Jian Min. (2013)
Following the success of Global Positioning System (GPS) in outdoor localization, the attention has shifted to indoor localization and its applications. Due to the very different wave propagation effects indoors, outdoor localization techniques are unable to obtain accurate results indoors.